Contribution of demography to economic growth - Miguel Sánchez-Romero; Gemma Abio; Concepció Patxot; Guadalupe Souto (SERIEs - Journal of the Spanish Economic Association, 2018)
From 1850 to 2000, in Western European countries life expectancy rose from 30-40 to 80 years and the average number of children per woman fell from 4 to 5 children to slightly more than one. To gauge the economic consequences of these demographic trends, we implement an overlapping generations model with heterogeneity by level of education in which individuals optimally decide their consumption of market- and home-produced goods as well as the time spent on paid and unpaid work. We find that around 17% of the observed increase in per-capita income growth from 1850 to 2000 was due to the demographic transition. Around 50% of the demographic contribution is explained by the increase in the average productivity per worker (productivity component), which arises from the change in the population's age structure and the rise in households' saving rate. The remaining 50% is explained by the higher growth rate of workers relative to the total population (translation component).
Keywords: D58; E27; J11; N30; 330; Demographic dividend; Fertility; Mortality; Per-capita income growth; Overlapping generations